2017
DOI: 10.1002/cjs.11324
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of a generalized linear mixed model for response‐adaptive designs in multi‐centre clinical trials

Abstract: Response‐adaptive designs are important alternatives to equal allocation in clinical trials because equal treatment allocation has been found to have ethical issues. In this article we discuss the implementation of response‐adaptive designs in multi‐centre clinical trials. We develop a generalized linear mixed model (GLMM) for analyzing data obtained from multi‐centre clinical trials and use the maximum likelihood (ML) approach to estimate the model parameters. We apply influence function techniques to derive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Selvaratnam et al. () have described how the allocation function of DBCD developed by Hu and Zhang () can be used in a RA design to assign treatments to patients in a way that targets the odds‐ratio‐based limiting allocation proportion ρfalse(PAS,PBSfalse)=OR(PAS,PBS)1+OR(PAS,PBS),where PAS and PBS are the success probabilities for those patients assigned to treatment A and B , respectively, and ORfalse(PAS,PBSfalse)=PAS(1PAS)(1PBS)PBS.This odds‐ratio‐based RA design was used in our simulation studies for comparison with CARA and CR designs due to its similarity in formulation to the CARA design we have also used in our simulation. Concerning the assignment of treatments based on CARA design, suppose that the minimum number of observations required for finding a unique solution to the ML estimating equation is n 0 .…”
Section: The Logit Model and Parameter Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…Selvaratnam et al. () have described how the allocation function of DBCD developed by Hu and Zhang () can be used in a RA design to assign treatments to patients in a way that targets the odds‐ratio‐based limiting allocation proportion ρfalse(PAS,PBSfalse)=OR(PAS,PBS)1+OR(PAS,PBS),where PAS and PBS are the success probabilities for those patients assigned to treatment A and B , respectively, and ORfalse(PAS,PBSfalse)=PAS(1PAS)(1PBS)PBS.This odds‐ratio‐based RA design was used in our simulation studies for comparison with CARA and CR designs due to its similarity in formulation to the CARA design we have also used in our simulation. Concerning the assignment of treatments based on CARA design, suppose that the minimum number of observations required for finding a unique solution to the ML estimating equation is n 0 .…”
Section: The Logit Model and Parameter Estimationmentioning
confidence: 99%
“…We note that to implement CARA designs, a user must first identify a suitable ideal model for the relationship between the response, treatment assigned to each patient and covariates. An initial model is however not required to implement RA designs (see Rosenberger et al., and Selvaratnam et al., ). The absence of sufficient data at the initial stage of a trial makes the identification of a suitable model a challenging task since the primary concern at the initial stage of a trial is the selection of a suitable design for treatment assignment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, various adaptive designs for treatment assignments which satisfy the ethical principles of clinical trials have been developed and found to be useful alternatives to completely randomized designs. See for instance, Selvaratnam, Oyet, Yi and Gadag (2017) for a recent discussion of examples of adaptive designs such as response adaptive (RA), covariate adaptive (CA) and covariate-adjusted response adaptive (CARA) designs. Since patients react differently to a given treatment, it has become increasingly important to also account for the effect of certain characteristics or covariates of individual patients as well as treatmentby-covariate interaction on the response of patients during treatment comparisons.…”
Section: Introductionmentioning
confidence: 99%